O design de interiores acessível : projecto de uma cozinha acessível a pessoas que se deslocam em cadeira de rodas - Lima, Ana Rita, 1993- (2018)
With the present investigation we intend to find out how a kitchen can be accessible to people in wheelchair. In order to achieve this objective it is necessary to understand this type of disability and what causes this inaccessibility. As such, the position of Design to Accessibility and the problems presented by most of the kitchens these days will be analyzed so that we can understand why they do not meet the needs of these users. This research has been divided into three parts that interconnected will answer the main question. In the first part the issue of disability is analyzed, as well as its current position in Design. In the second part a review of the literature on the kitchen, its constituents and possible solutions is made so that it becomes accessible to its target audience. The third part proposes a project of an accessible kitchen that can fulfil the proposed objectives in the absence of concrete and ideal solutions. After the analysis is over, we can conclude that Design reveals concerns regarding accessibility issues and that these should be implemented in the methodologies of designers. The solutions of accessible kitchens found are not as complete or ideal, however, they allow to verify that there are many configurations and equipment available to realize this project, and for that it is need that the market offers more alternatives but essentially that there will had a bigger concern with the needs of each individual user, through research and dialogue with himself